Prevalence of psychological distress and its associated factors among medical relief workers involved in the 2014 flood disaster in Kuala Krai Kelantan - Kumar, Punita A/P Udaya (2017)
This study aims to determine the prevalence of psychological distress and its associated factors among medical relief workers who provided service in Hospital Kuala Krai, Kelantan during the 2014 major flood disaster. It is a cross sectional observational study conducted among 160 medical relief workers 8 months after the disaster occurred. Socio-demographic data was collected using a Proforma, while PTSD, Depression, Anxiety and Stress were assessed using the Impact Event Scale- Revised and DASS-21 respectively. Coping methods were assessed using the Brief COPE questionnaire. All the scales used were in Malay version and self-reported. The prevalence of PTSD was 12.5%, Depression 18.1%, Anxiety 38.8% and 18.1%. Using multiple logistic regression analysis, education (ORadj 0.04, 95% CI 0.00- 0.50, p = 0.013) and experience of traumatic event (3.86, 95% CI 1.11-13.41, p=0.034) were found to be significantly associated with PTSD. For depression, total household income per month (ORadj 0.99, 95% CI 0.998-0.99, p=0.002), number of hours per day of relief work (ORadj 0.90, 95% CI 0.81-0.99, p=0.032), and use of Emotional Support (ORadj 2.58, 95% CI 1.13-5.88, p=0.024) were found to be significant. Previous flood experience (ORadj 0.20, 95% CI 0.06-0.65, p=0.08), number of hours per day of relief work (ORadj 0.92, 95% CI 0.86-0.98, p=0.011) and use of Emotional support (ORadj 2.14, 95% CI 1.30-3.52, p=0.003) were found to be significant for Anxiety. Finally, occupation (ORadj 0.25 95% CI 0.09-1.69, p=0.007) use of Behavioral Disengagement (ORadj 1.61, 95% CI 1.06-2.45, p=0.025) and Self-blame (ORadj 2.31, 95% CI 1.48-3.88,p=0.002) were found to be significantly associated with Stress. In conclusion, medical relief workers were vulnerable topsychological distress and had increased prevalence of PTSD, Depression, Anxiety and Stress.